Introduction and comparison of education in the Tradiciones peruanas - Pauca Huallpar, Adeline Juliana (2019)
This article will discuss the tradition «El latín de una limeña». The goal is to analyze the education in that context and compare it with the current Peruvian education. To do so, the importance of Latin in the past and today in Peru; the study of this language for three or four years in school, which is not done in current schools; examples of the use of Latin in everyday life in both cases, such as in religion (masses), medicine (doctors’ prescriptions that made patients dizzy) and in the daily conversation will be discussed. Some comparisons will also be made with the careers of Translation (great women translators such as Doña María Juana Calderón stand out here) and of Literature (the Gongorism of that time and the outstanding writers).